Supply chain intelligence and its impact on competitive strategy and performance of businesses in Malaysia - Jaharuddin, Nor Siah (2012)
The business environment has become more competitive due to advancement in technology and globalization. Since, competition nowadays involves the activities amongst supply chains (Christopher, 1992; Cox, 1999), these influenced greatly how business organizations strive for business success. The emergence of competitive intelligence (CI) and supply chain management (SCM) in dealing with such circumstances has brought the need to study further on the acquisition and usage of intelligence in supply chain integration. Building on the relevant literature, this study discusses the concept of SCI and its components in creating a sustained competitive advantage. Since, there is little empirical work on the impact of SCI on competitive strategy and the subsequent effects on the performance; this study fills that gap by studying the role of SCI on its networks and competitors. Ultimately, the framework provides possible relationships that can be evaluated to assess the value of the SCI function to future firm performance. Apart from extensive empirical literature review, a focus group was employed as a preliminary study to construct the SCI components and subsequently the development of the questionnaire. A questionnaire survey was used to gather data for this quantitative study. Sample list was drawn from a directory of Federation of Malaysian Manufacturers (FMM) with 174 participating organizations. All research questions and objectives were answered by performing appropriate descriptive and inferential statistical analyses such as hierarchical and multiple linear regressions (MLR). The findings were further supported from post-interviews with eight selected organizations based on size, ownership, and manufacturing sector. SCI components are consisting of external environment intelligence, supply chain integration, research and development, sales and marketing, and human resources and capabilities. The findings revealed that regardless of size and ownership, all organizations do gather SCI data and the processes are not necessarily confined to a specific department. The findings also indicate that there are significant positive relationships between SCI and competitive strategy. This implies that most of the easily accessible SCI (resources and capability, research and development, and external environment) are significantly used in formulating strategies of the organization. In addition, competitive environment and intelligence culture (from organizational characteristics) are found to have moderating effects in the relationship between SCI and competitive strategy, while organizational efforts, managerial perceptions, and size are insignificant. The mediating role played by competitive strategy help to explain the contribution and underlying process that are responsible for the relationship between SCI and performance. The findings of this study have significantly contributed to both theory and practices by bring in the strategic role of SCI as a vital ingredient to facilitate the formulation of competitive strategy, thus strengthen the supply chain integration and its performance.